Food hunting: a search of the past and dream of the future - Hendijania, Roozbeh Babolian; Boo, Huey Chern (Elsevier Ltd, 2014)
The number of people who travel with the primary reason for gastronomic experience, termed gastronomes, is in the rise. This group of consumers may travel far or near for the purpose of food or gastronomy experience. This niche travellers are recognized as a group of individuals who are highly involved in the related activity. They exerted immense impact on others through their words in food-related TV shows, tourism websites, and food blogs. Regrettably, studies examined this group of consumers are limited. The main of objective of the current research was driven by the pressing need to reveal the underlying psychology of gastronomes travel with the purpose of food hunting. This research adopted Zaltman Metaphor Elicitation Technique (ZMET), an emerging powerful qualitative method, to understand the gastronomes’ food hunting behavior through their own voice. The participants were recruited through purposive and snowball sampling and they came from different states in Malaysia. Face-to-face interviews (requiring approximately 90 to 120 minutes) were scheduled one to two weeks after the participants were recruited and were requested to search for self-relevant pictures. The employment of ZMET proved to be fundamental in digging deeply into the mind of the participants and extracting some very deep-seated meanings from the gastronomes that they did not know themselves prior to the interview. The results from this study provide a series of opportunities for future researches.